Analisis Tindak Tutur Ilokusi Dominan Dalam Komentar Masyarakat Terhadap Video Kekerasan Aparat Terhadap Pelajar Di Media Sosial - Cristin Ameria; Delima Br Manullang; Lusia Gita Vanesa; Rismauli Natalia; Syahiba Nadin Yusuf; Oky Fardian Gafari; Herning Puspitarini (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the dominant types of illocutionary speech acts found in public comments on social media related to the video of violence by Brimob officers against students in Tual City. This issue is important because the use of excessive force, or police brutality, triggers strong emotional reactions on digital platforms like TikTok. Using a descriptive qualitative approach and Searle's pragmatic theory, this research examines netizen comments collected through documentation and note-taking. The results show that expressive and directive illocutionary speech acts dominate the conversation. Expressive acts serve as a means for shared anger and empathy, while directive acts manifest as public demands for a thorough investigation. These findings suggest that language on social media works not only as a communication tool but also as a method of social control and mass mobilization that pressures law enforcement to uphold accountability and professionalism.